2018
DOI: 10.3389/fpsyg.2018.01254
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Narcissus: Just a Myth? Narcissism Moderates the Age-Loneliness Relationship in Older Age

Abstract: Objective: Recent research has indicated that sub-clinical narcissism may be related to positive outcomes in respect of mental and physical health, and is positively related to an extended lifespan. Research has also indicated narcissism levels may decline over the lifespan of an individual. The aims of the present study were to investigate these issues, exploring age-related differences in levels and outcomes of narcissism. Specifically, narcissism’s relationship with loneliness, a deleterious but pervasive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…The negative associations between age and narcissism found in the present study is in line theories that suggest narcissism declines across adulthood and with previous cross-sectional and longitudinal evidence examining one of the focal eight measures separately (e.g., Barlett & Barlett, 2015;Carter & Douglass, 2018;Foster et al, 2003;Grosz et al, 2019;Hill & Roberts, 2012;Roberts et al, 2010;Wetzel et al, 2020;Wilson & Sibley, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The negative associations between age and narcissism found in the present study is in line theories that suggest narcissism declines across adulthood and with previous cross-sectional and longitudinal evidence examining one of the focal eight measures separately (e.g., Barlett & Barlett, 2015;Carter & Douglass, 2018;Foster et al, 2003;Grosz et al, 2019;Hill & Roberts, 2012;Roberts et al, 2010;Wetzel et al, 2020;Wilson & Sibley, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Prior research has shown that narcissism levels decrease with age (Foster, Campbell, & Twenge, 2003; Trzesniewski & Donnellan, 2010), and narcissistic aggression might also decrease with age. Previous research has shown that people over age 65 have low narcissism levels (Carter & Douglass, 2018), which is outside the mean age range included in this meta-analytic review. Thus, future research should examine narcissistic aggression in older people.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with evolutionary theory, several scholars have suggested that narcissism levels reach a developmental high in adolescence (e.g., Bleiberg, 1994), and decrease across the life span (Foster, Campbell, & Twenge, 2003, Trzesniewski & Donnellan, 2010, until they reach a developmental low in older age (Carter & Douglass, 2018;Robins et al, 2002). This meta-analytic review explores whether age moderates the relation between narcissism and aggression.…”
Section: Participant Characteristicsmentioning
confidence: 90%
“…In line with this, Gąsiorowska et al [ 44 ] reported that antagonistic narcissism was associated with increased loneliness and less social support in a community sample ( N = 662). Finally, Carter and Douglass [ 45 ] observed that loneliness increased with age, whereas narcissism decreased in middle-aged and older-aged adults ( N = 100 in each group). Furthermore, narcissism moderated the relationship between loneliness and age, leading to the authors’ conclusion that a certain degree of narcissism may even be protective against feeling lonely which underlines the relevance to further investigate the interplay of narcissism and loneliness.…”
Section: Narcissistic Personalitymentioning
confidence: 99%